2019
DOI: 10.1016/j.cmet.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

PML-Regulated Mitochondrial Metabolism Enhances Chemosensitivity in Human Ovarian Cancers

Abstract: SummaryHigh-grade serous ovarian cancer (HGSOC) remains an unmet medical challenge. Here, we unravel an unanticipated metabolic heterogeneity in HGSOC. By combining proteomic, metabolomic, and bioergenetic analyses, we identify two molecular subgroups, low- and high-OXPHOS. While low-OXPHOS exhibit a glycolytic metabolism, high-OXPHOS HGSOCs rely on oxidative phosphorylation, supported by glutamine and fatty acid oxidation, and show chronic oxidative stress. We identify an important role for the PML-PGC-1α axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
187
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(199 citation statements)
references
References 59 publications
12
187
0
Order By: Relevance
“…In turn, PGC-1α increases the synthesis of ETC complexes, thereby promoting mitochondrial respiration. Interestingly, this pathway leads to increased response to conventional chemotherapies in the high OXPHOS HGSOCs [39]. On the other hand, we found that cisplatin resistant HGSOC cells lines were more oxidative than their sensitive counterpart, and that inhibition of OXPHOS restored cisplatin sensitivity [40].…”
Section: Metabolic Reprogramming Oxidative Stress and Chemoresistancmentioning
confidence: 72%
“…In turn, PGC-1α increases the synthesis of ETC complexes, thereby promoting mitochondrial respiration. Interestingly, this pathway leads to increased response to conventional chemotherapies in the high OXPHOS HGSOCs [39]. On the other hand, we found that cisplatin resistant HGSOC cells lines were more oxidative than their sensitive counterpart, and that inhibition of OXPHOS restored cisplatin sensitivity [40].…”
Section: Metabolic Reprogramming Oxidative Stress and Chemoresistancmentioning
confidence: 72%
“…Indeed, it has been demonstrated that mutated BRAF negatively regulated oxidative metabolism in melanoma cells [186], while BRAF inhibitors enhanced dependence of melanoma cells on the oxidative phosphorylation (OXPHOS) [186,187]. It has been hypothesized that chemosensitivity of OXPHOS high cancer cells could rely on ROS accumulation and might be potentially executed by induction of ferroptosis [188]. This suggests that a metabolic switch induced by BRAFi can sensitize melanoma cells to ferroptosis-inducing agents, and SCL7A11 has been suggested as a marker of the susceptibility of metastatic melanoma cells to ferroptosis [189].…”
Section: Ferroptosis In Melanomamentioning
confidence: 99%
“…GPX4 dependency on erastin induced ferroptic cell death occurs in cell-type-specific manner [10], though the strength of this vulnerability varies in a cell-specific manner. As such, a variety of cellular and molecular components and processes, such as metabolic heterogeneity [11], mesenchymal properties [9], differentiation status [12], p53 status [13], transcription factors [14,15], signaling pathways (e.g. MAPK [16], ATM [17] or YAP [18]), integrins [19], GSH regulators [20], and levels of monounsaturated fatty acid [21], have been examined as determinants of ferroptosis vulnerability in a diverse range of cell model systems.…”
Section: Introductionmentioning
confidence: 99%